The Effect of Learning Motivation on Chinese Language Learning Achievement at STBA-PIA College Student - Alemina Br Perangin-angin (UIN Sumatera Utara, 2016)
Learning Motivation is one of the factors that influence the learning achievement. Encourage student learning motivation for learning activities, determine the direction of action and selecting actions that are beneficial in achieving academic achievement in maximum. A student with a high degree of intelligence may fail to achieve maximum performance if there is lack of motivation to learn. The purpose of this study was to determine whether there is influence learning motivation on learning achievement.This study research is using Ex post facto design, by simple random sampling technique. The study population of 150 students of 5th semester chinese literary STBA-PIA academic year 2013/2014 with a sample of 30 students. Methods of data collection is using questionnaires of learning motivation and Score of the course “Zonghe” F2. Data Analysis is using T-test.Data analysis showed that test T is t count equal to 8.89 and t table (dk=28) of 1.70. t count > t table (8.89 > 1.70), which means it shows the significant influence between learning motivation on learning achievement of semester 5 sutdent in STBA-PIA. The significant level of 5%. Ha accepted Ho rejectedKeywords: Learning motivation, learning achievements